一种舰载无人机光电引导着舰系统及着舰方法 (2022)
本发明公开了一种舰载无人机光电引导着舰系统，包括舰上观测组件和反光板；所述反光板固设于无人机机身，和/或，机翼上；所述舰上观测组件包括常平台、跟踪转台、红外热像仪、激光测距仪和控制单元；所述常平台固设于舰艇甲板上；所述跟踪转台安装于常平台上，且跟踪转台可沿竖直轴线做转动式运动；所述红外热像仪和激光测距仪安装于跟踪转台上，且红外热像仪和激光测距仪可做俯仰式运动；所述控制单元获得跟踪转台的方位转角数据、红外热像仪和激光测距仪的俯仰转角数据、激光测距仪检测的无人机的相对距离后，通过运算获得无人机的侧偏距、待飞距、相对甲板高度信息并引导其至着陆点着舰。 The invention discloses a ship-borne unmanned aerial vehicle photoelectric guiding landing system, which comprises an on-board observation assembly and a reflector. The reflector is fixed on a fuselage and/or a wing of the unmanned aerial vehicle. The on-board observation module comprises a constant platform, a tracking turntable, an infrared thermal imager, a laser rangefinder and a control unit;the constant platform is fixedly arranged on the deck of the naval vessel; the tracking turntable is installed on the constant platform, and the tracking turntable can rotate along a vertical axis; the infrared thermal imager and the laser rangefinder are installed on the tracking turntable, and the infrared thermal imager and the laser rangefind